Lucy and the firestone - Crebbin, June.; Dunbar, Polly (London : Walker Books, 2004)
The firestone in the Royal Lighthouse has gone out! Lucy, the Lighthouse Keeper's daughter, must follow the clues in the riddle to find another one before it's too late.